Psychopath of Ma'alk Reflected in Dan Brown's Novel the Lost Symbol (2009): A Psychoanalysis Approach - Andrianto, Agung; , Dewi Candraningrum, S.Pd., M.Ed., Phil. Dr (2017)
This study is aimed to show Maalk's character in The Lost Symbol novel (2009) by using psychoanalysis approach. It is finish by establishing two objects: the first is analyzing the novel based on structural elements And the last is analyzing the main character based on psychoanalysis approach. This research is descriptive qualitative research. Type of the data of the study is text taken from two data sources: primary and secondary. The primary data source is the Lost Symbol Novel written by Dan Brown release in 2009. While the secondary data sources are other materials taken from books, journals, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes two following conclusions. First, based on the structural analysis of each element, its shows that the character and characterization, setting of place, setting of time,plot, point of view, and theme are related to each other and form of unity. Second, based on the psychoanalysis approach reflected in the main character Ma'alkh, The most data which appear is Grandiose Self-Worth, the researcher finds seven data in the novel. Those are followed by Conning And Manipulativeness, Lack of Remorse or Guilt, Criminal Versatility. Those three characteristics have same number of data, six data. Then Pathological Lying, Callousness and Lack of Empathy and Poor Behavioral Controls have same data, two data. In the last, there are data that just have one data, namely: Need for Stimulation or Proneness to Boredom, Parasitic Lifestyle, Promiscuous Sexual Behavior, Early Behavior Problems and Failure to Accept Responsibility for Own Actions.